2006
DOI: 10.1515/cam.2006.020
|View full text |Cite
|
Sign up to set email alerts
|

Integrating patients' nonmedical status in end-of-life decision making: Structuring communication through 'conferencing'

Abstract: This paper considers the nonmedical status of patients in end-of-life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Family members reported that they trusted nurses who introduced themselves to the family, explained equipment, and were willing to talk [28]. Nurses also identified the importance of establishing a rapport with families [12, 35, 44, 45]. Nurses reported taking time to introduce the family to the oncoming shift nurse to show confidence in that nurse and facilitate the shift change [46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family members reported that they trusted nurses who introduced themselves to the family, explained equipment, and were willing to talk [28]. Nurses also identified the importance of establishing a rapport with families [12, 35, 44, 45]. Nurses reported taking time to introduce the family to the oncoming shift nurse to show confidence in that nurse and facilitate the shift change [46].…”
Section: Resultsmentioning
confidence: 99%
“…Would he say, stop, that's enough” [22] (page 301)? Although Sorensen and Iedema [45] found that nurses were not routinely included in family meetings and were not privy to what physicians had told the family, one nurse expressed that when attending a family meeting he/she would “put in my five cents' worth…at the end of it” (page 191). …”
Section: Resultsmentioning
confidence: 99%
“…These themes have since been written about extensively (Iedema et al. 2004, 2005, Sorensen & Iedema 2006, 2007, 2008). Homing in on nurses’ contribution to organizing intensive care work, three focus groups were conducted with less experienced (12), intermediate experienced (8) and experienced (9) nurses, and interviews were conducted with unit nurse managers (4) and a senior nurse manager (1).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in clinical practice there are structural and organizational problems between different disciplines in clinical practice, including, importantly, between medicine and nursing (Manias & Street 2001a,b). We have already argued that structuring communication at key points in the patient’s trajectory is important for good intensive and end‐of‐life care (Sorensen & Iedema 2006), but the question that arises here is, how do nurses become empowered to contribute to team functioning from a position of strength?…”
Section: Introductionmentioning
confidence: 99%
“…Interpretations of values expressed in decisions and those represented in patients' life stories are subjective, and the reliability of those interpretations is a function of many things, including the quality and reliability of the relationship between a patient and physician (Eliott and Olver 2005;Sorensen and Iedema 2006). A physician must have an understanding of what is important to Ms. D if she is to be reasonably certain that her decision to forego a gastrostomy tube is appropriate for her, Dr. W must forge a relationship with Mr. A to learn that he is deeply bereaved about his decline in kidney functioning, and Dr. P must not dismiss Mr. B if she is to properly appreciate his desperation.…”
Section: Clarifying the Roles Of Consulting Psychia-trists In Inpatiementioning
confidence: 99%